Long noncoding RNA MyD88 functions as a promising diagnostic biomarker in hepatocellular carcinoma - Wang, Zhihuai; Gao, Peng; Sun, Weijun; Rehman, Adeel ur; Jiang, Jiakai; Xu, Suobao; Xue, Cailin; Zhu, Chunfu; Qin, Xihu (Frontiers in Endocrinology, 2023)
Background: Hepatocellular carcinoma (HCC) is one of the most frequent malignancies. Alpha-fetoprotein (AFP) has some limitations in diagnosing early HCC. Recently long non-coding RNAs (lncRNAs) showed great potential as tumor diagnostic biomarkers, and Lnc-Myd88 was previously identified as carcinogen in HCC. Here we explored its diagnostic value as plasma biomarker. Materials and methods: Quantitative real-time PCR was adopted to detect Lnc-Myd88 expression in plasma samples of 98 HCC patients, 52 liver cirrhosis (LC) patients and 105 healthy people. The correlation between Lnc-Myd88 and clinicopathological factors were analyzed through Chi-square test. Receiver operating characteristic (ROC) curve was used to analyze the sensitivity, specificity, Youden Index and area under the curve (AUC) of Lnc-Myd88 and AFP alone and in combination for the diagnosis of HCC. The relationship between Myd88 and immune infiltration was analyzed by ssGSEA algorithm. Results: Lnc-Myd88 was highly expressed in plasma samples of HCC and HBV-associated HCC patients. Lnc-Myd88 had better diagnostic value than AFP in HCC patients using healthy people or LC patients as control (healthy people, AUC: 0.776 vs 0.725; LC patients, AUC: 0.753 vs 0.727). The multivariate analysis showed Lnc-Myd88 had great diagnostic value for distinguishing HCC from LC and healthy people. Lnc-Myd88 had no correlation with AFP. Lnc-Myd88 and AFP were the independent diagnostic factors for HBV-associated HCC. The AUC, sensitivity and Youden index of the combined diagnosis of Lnc-Myd88 and AFP was higher than that of Lnc-Myd88 and AFP alone. The ROC curve of Lnc-Myd88 for the diagnosis of AFP-negative HCC was plotted with a sensitivity of 80.95%, a specificity of 79.59%, and an AUC value of 0.812 using healthy people as control. ROC curve also presented its great diagnostic value using LC patients as control (Sensitivity: 76.19%; Specificity: 69.05%; AUC value:0.769). Lnc-Myd88 expression was correlated with microvascular invasion in HBV-associated HCC patients. Myd88 was positively correlated with infiltrating immune cells and immune-related genes. Conclusion: The high expression of plasma Lnc-Myd88 in HCC is distinct and could be utilized as promising diagnostic biomarker. Lnc-Myd88 had great diagnostic value for HBV-associated HCC and AFP-negative HCC, and it had higher efficacy in combination with AFP.